2022
DOI: 10.3390/fishes7050250
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Seasonal Differences in Fish Populations in Laizhou Bay Using Environmental DNA and Conventional Resource Survey Techniques

Abstract: In recent years, environmental DNA (eDNA) technology has gradually improved, and it has been increasingly used to monitor marine fish. The decline and seasonal fluctuations of fish resources in Laizhou Bay, Bohai were studied using eDNA technology and compared with the results of conventional fish resource survey methods. In November 2020 (autumn), March 2021 (spring), and July 2021 (summer), 12 samples were collected each quarter in Laizhou Bay and adjacent waters for a total of 36 eDNA samples, and 47 fish s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Consistent with previous research, the surface and bottom communities had a lower diversity in spring, whereas a higher diversity was observed in summer [37]. Biological diversity is closely related to the environment, especially in the estuary ecosystem [38].…”
Section: Fish Diversity In Yellow River Estuarysupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous research, the surface and bottom communities had a lower diversity in spring, whereas a higher diversity was observed in summer [37]. Biological diversity is closely related to the environment, especially in the estuary ecosystem [38].…”
Section: Fish Diversity In Yellow River Estuarysupporting
confidence: 90%
“…In our study, temperate, subtropical, and tropical species accounted for 36%, 33%, and 31%, respectively, within the entire study area. In Laizhou Bay, the number of species preferring warm water was highest in all the seasons [37]. Thus, from the spring to the summer, as the water temperature rises, the diversity of fish species gradually increases.…”
Section: Fish Diversity In Yellow River Estuarymentioning
confidence: 94%
See 2 more Smart Citations
“…We found that among the taxa detected by the eDNA technology across different orders, there were obvious differences from the historical records (Figure 3). Specifically, the number of Diptera, Neuroptera and Lepidoptera detected by the eDNA technology was higher than in the historical records, which may be because the eDNA technology performs a species annotation at the molecular level and could monitor some species that were not easily detected using conventional techniques [48]. However, it was also slightly insufficient in the monitoring of other macroinvertebrates, such as Megaloptera, Hemiptera and Trichoptera.…”
Section: Resultsmentioning
confidence: 86%